Influence of Process Errors on the Tool Load in Microblanking of Thin Metal Foils with Silicon Punches - Hildering, Sven; Engel, Ulf; Merklein, Marion (9th International Conference on MicroManufacturing (ICOMM 2014), 2014)
Influence of Process Errors on the Tool Load in Microblanking of Thin Metal Foils with Silicon Punches.
LFT Import::2019-07-29 (2011)